Analysis of the Development of Accounting Information Systems Research with Bibliometric Analysis - Maryanti, Istinganah Eni (Enigma in Economics, 2024)
Accounting information systems (AIS) play an important role in supporting decision-making, improving operational efficiency, and increasing organizational accountability. Along with the development of information and communication technology, AIS research continues to grow rapidly. Bibliometric analysis is an appropriate method for mapping the development of AIS research. This research uses bibliometric analysis methods with AIS scientific publication data collected from Scopus and Web of Science during the 2010-2023 period. Data was analyzed with VOSviewer to map research trends, collaboration between institutions, and dominant research topics. AIS research is experiencing rapid growth with a primary focus on systems development, technology adoption, and its impact on organizational performance. Collaboration between research institutions is still low, and there are several research topics that are minimally researched. AIS research shows a focus on technology development, adoption, and impact on organizational performance. Collaboration between institutions is still low, and there are research topics that are minimally researched.